Government Openness and Public Trust: The Mediating Role of Democratic Capacity. (28th October 2020) - Schmidthuber, Lisa; Ingrams, Alex; Hilgers, Dennis
Abstract: The open government paradigm implies that public processes are becoming more transparent, public information is available online, and citizens and nongovernmental organizations are encouraged to interact with public administration through new platform‐based forms of participation and collaboration. Though these governmental efforts to open up organizational procedures to the public are meant to strengthen the relationship between citizens and the government, empirical evidence is currently sparse and mixed. This article argues that positive impacts of openness depend on citizen's democratic capacity defined as the individual sense of empowerment to influence governmental systems. By matching individual survey data from the European Social Survey with secondary institutional data, the authors investigate the relationship between individual‐ and structural‐level variables. Findings indicate that structural openness is, in general, positively associated with higher trust. Further, the effect of openness on public trust is partially mediated by an individual's perception that they have meaningful opportunities for political participation.